The relationship and impact of ASEAN-5 stock market towards Malaysia Stock Market: analysis based on Main Index / Aiman Zulkifli - Zulkifli, Aiman (Faculty of Business and Management, 2015)
The interdependency of the stock market between countries has been investigated widely by the researchers especially after the Asian Financial Crisis 1997 such as Majid, Yusof and Razal (2007), Arifin and Syahruddin (2011), Sukcharoensin and Sukcharoensin (2013). This study attempts to extend the knowledge of the relationship and impact of Straits Times Index STI, Jakarta Stock Exchange Composite Index, Philippines Stock Exchange PSEi Index, and Stock Exchange of Thailand SET Index towards FTSE Bursa Malaysia KLCI Index. Simple linear regression and multiple linear regression was applied in this study to determine the relationship between the stock market of ASEAN-5 countries. The result obtained in this study indicates there is a positive significant relationship and impact of Straits Times Index STI, Jakarta Stock Exchange Composite Index, Philippines Stock Exchange PSEi Index, and Stock Exchange of Thailand SET Index towards FTSE Bursa Malaysia KLCI Index.